Examining the Effect of Brand Image, Price and WoM Communication on Purchase Decisions: A Case Study of Rinnai Gas Stove - Purba, Rakhmawati; Dewi, Kumala Vera; Siregar, Aisyah; Damanik, Sri Winda Hardiyanti (International Journal of Business, Economics & Financial Studies, 2023)
The substitution of cooking utensils from kerosene stoves to gas stoves causes housewives to consider various brands of stoves in making their purchasing decisions for their daily cooking needs for their families. This study aims to determine the effect of brand image, price, and word-of-mouth communication on the Rinnai Gas Stove Purchase Decision on Housewives in Dusun VI, Kuta Baru Village. The independent variables of this study consisted of brand image, price and word-of-mouth communication, while the dependent variable was purchasing decisions. This research is a quantitative approach. The primary data was obtained through questionnaire answers from 65 respondents who use the Rinnai gas stove in Hamlet VI, Kuta Baru Village. Data were analyzed using multiple linear regression analysis methods. The results of the analysis show that Brand Image (X1) affects the Purchasing Decision variable (Y), Price (X2) does not affect the Purchasing Decision (Y), word-of-mouth Communication (X3) affects the Purchasing Decision (Y) and Brand Image (X1), Price (X2) and WoM Communication (X3) influence simultaneously (simultaneously) on the Purchase Decision Variable (Y).